Minat Belajar Anak dan Respon Orang Tua terhadap Pendampingan Belajar pada Masa Covid-19 (Studi Kasus Kecamatan Pahandut Palangka Raya) - Hadi Kusuma, Muhammad Prayoga; Setyowati, Ais Rantauni; Wati, Helda; Tumini, Tumini; Maulida, Elyami; Raniah, Nor; Fitriani, Amelia; Damayanti, Annisa; Hasbi, Artani; Yusuf, Muhammad; Hujjatusnaini, Noor (LP2M IAIN Sultan Amai Gorontalo, 2020)
This study aims to determine student interest in learning and parents' responses to learning assistance at home during the Covid-19 pandemic in Pahandut Palangka Raya District, Central Kalimantan. This research is a quantitative descriptive study with a survey method, in which the survey data is measured quantitatively and then the statistical correlation is sought. The research sample of students and parents of students respectively as many as 348 people. The sampling technique was purposive sampling, in the Pahandut District, Palangka Raya. The results of the study reported that students' interest in learning was in the